Examining Disproportionality in School Discipline for Aboriginal Students in Schools Implementing PBIS. (September 2014) - Greflund, Sara; McIntosh, Kent; Mercer, Sterett H.; May, Seth L.
The purpose of this exploratory study was to investigate the extent to which students with Aboriginal status receive disproportionate rates of office discipline referrals (ODRs) and more severe administrative consequences relative to students without Aboriginal status. The participants were 1, 750 students in five rural British Columbia and Alberta elementary and middle schools implementing Positive Behavioral Interventions and Supports (PBIS). Binary multilevel logistic regression was used to determine to what extent disproportionality was present. Contrary to hypotheses, students with Aboriginal status were no more likely to receive ODRs than students without Aboriginal status. Students with Aboriginal status were not statistically significantly more likely to receive suspensions and harsh administrative consequences from ODRs. Potential factors for these encouraging findings include the small sample, the Canadian context, and implementation of PBIS with culturally responsive adaptations for students from Aboriginal cultures. Results are discussed with respect to reducing disproportionate outcomes for Aboriginal students in schools.